2019
DOI: 10.1186/s12904-019-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life and palliative care of patients on maintenance hemodialysis treatment: a focus group study

Abstract: BackgroundDespite complex illness trajectories and a high symptom burden, palliative care has been sub-optimal for patients with end-stage kidney disease and hemodialysis treatment who have a high rate of hospitalization and intensive care towards end of life. There is a growing awareness that further development of palliative care is required to meet the needs of these patients and their family members. In this process, it is important to explore healthcare professionals’ views on provision of care. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
(51 reference statements)
5
21
0
9
Order By: Relevance
“…Individuals with ESKD, cared for in renal centres where palliative care services are well-established, choose palliative care more often than centres without palliative care services [2,16]. It has been reported that individuals with ESKD would prefer to be given adequate information about the condition and their treatment options, including palliative care, at an earlier stage of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with ESKD, cared for in renal centres where palliative care services are well-established, choose palliative care more often than centres without palliative care services [2,16]. It has been reported that individuals with ESKD would prefer to be given adequate information about the condition and their treatment options, including palliative care, at an earlier stage of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care for ESKD has been de ned as "a transition from a conventional disease-oriented focus on dialysis as a rehabilitative treatment to an approach prioritizing comfort and alignment with preferences and goals of care to improve quality of life and reduce symptom burden" (1,2). It comprises interventions that focus on slowing the deterioration of kidney function, minimising the risk of adverse events, shared decision-making, active symptom management, detailed communication, including advance care planning, psychological, social and family support, and cultural and spiritual care, but does not include RRT (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…This is, especially, more profound in lowerand middle-income countries (LMICs) where nancial, geographical and infrastructural challenges affect the provision of e cient renal services (18)(19)(20)(21)(22). Inadequate information provision and delayed initiation of discussions on palliative care also remain key barriers to its utilisation as a treatment option for ESKD (2,17,23,24). Informal caregivers of individuals with ESKD, mainly relatives and friends, may also discourage clinicians' efforts at providing open and honest information about palliative care services (25).…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care for ESKD has been defined as "a transition from a conventional disease-oriented focus on dialysis as rehabilitative treatment to an approach prioritizing comfort and alignment with preferences and goals of care for to improve quality of life and reduce symptom burden" (1,2). This is increasingly becoming an accepted treatment choice and is highly recommended for individuals in whom renal replacement therapy (RRT) may offer little or no significant difference in terms of survival or quality of life (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of individuals with ESKD seeking care from renal centres where palliative care services are well-established and discussed choose palliative care (2,14). It has been reported that individuals with ESKD would prefer to be given adequate information about the condition and their treatment options, including palliative care, at an earlier stage of the disease (15).…”
Section: Introductionmentioning
confidence: 99%